Female-friendly toilets in schools in Burkina Faso: a mixed-methods study using photo-elicitation - Buitrago García, Teresa; Sawadogo, N. Hélène; Souares-Coutant, Aurélia; Koulidiati, Jean-Louis; Sié, Ali; Bärnighausen, Till; Langlotz, Sarah; McMahon-Rössle, Shannon A. (Journal of global health, 2022)
An absence of gender-sensitive sanitation facilities in schools and the negative effects this has on girls has been widely discussed among advocacy groups, though less examined in academic spheres. Drawing on triangulated data, we outline current challenges and espondent-driven solutions to enhance the female-friendly nature of toilets in a context of extreme poverty.
Gesehen am 22.11.2022